El FONPRODE: algunas implicaciones para la planificación y la gestión de la política de desarrollo - Cortés Fernández, Javier; González Pacheco, Francisco (Revista Española de Desarrollo y Cooperación, 2023)
Noting in its opening lines that FONPRODE is, at the same time, an opportunity and a challenge for Spanish cooperation, the article dedicates its first part to review the operations that can be funded paying special attention, due to it novelty, to financial cooperation operations and its requirements under the rules of FONPRODE. The second part of the article focuses on the analysis of certain issues related to the importance of strategic planning of operations that should be taken into account to ensure that financial cooperation provided by the FONPRODE is integrated as an instrument at the service of the Spanish development policy.